Penggunaan Metode Syllabic dalam Pembelajaran Bahasa Indonesia untuk Meningkatkan Keterampilan Membaca Permulaan Pada Kelas 1 MI Ma’arif Lemah Duwur Kuwarasan - Wardana, Reza Enisa; Rahma, Arum Aulia; Rahmawati, Putri Nurul; Syahidah, Amalia; Karmila, Ni'ma; Fatimah, Siti; Wardopo, Komper (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The main problem of this research is how to improve beginning reading skills through the application of the syllabic method in class 1A students at MI Ma'arif Lemah Duwur Kuwarasan. This research aims to determine the effectiveness of the syllable method in helping the development of beginning reading learning. This type of research is classroom action research (PTK) which consists of 2 cycles. The research procedures carried out include planning, implementing actions, observing and reflecting. The subjects in this research were 18 students in class 1A MI Ma'arif Lemah Duwur Kuwarasan. The research results showed that in cycle I the average aspect obtained was 74%. In cycle II there was an increase, the initial reading ability test results were 91%. The syllabic method can successfully improve the beginning reading skills of MI Ma'arif Lemah Duwur Kuwarasan students.